2023
DOI: 10.1038/s41415-023-5506-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral and maxillofacial injuries associated with e-scooter use at Broomfield Hospital: a cohort study of 24 months of data since e-scooter legalisation in the UK

Abstract: Introduction Rental electronic scooters (e-scooters) were legalised in July 2020 in the UK for use on public roads. This has led to higher numbers of emergency department (ED) attendances for head and neck injuries managed by the oral and maxillofacial surgical (OMFS) department. Aim The aim of this research is to assess the increase in e-scooter injuries requiring OMFS input and analyse factors and management associated. Method Data were collected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies on injuries related to the use of electric scooters conducted in cities where they are a popular means of transport have shown that the victims of accidents are usually men [24][25][26]. They account for 52% to 79% of victims [7,11,15,16,27,28]. They constituted 61.3% of the studied population.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on injuries related to the use of electric scooters conducted in cities where they are a popular means of transport have shown that the victims of accidents are usually men [24][25][26]. They account for 52% to 79% of victims [7,11,15,16,27,28]. They constituted 61.3% of the studied population.…”
Section: Discussionmentioning
confidence: 95%